Energy and the Environment - Ristinen, Robert A.; Kraushaar, Jack J.; Brack, Jeffrey T. (USA: Wiley, 2022)
"One of the Millenium Project's challenges is the energy challenge: How can growing energy demands be met safely and efficiently? Energy research and technology plays a pivotal role in addressing this challenge, and, therefore, there is a growing need for well-educated physicists and engineers who can translate research results into market- and environment-compatible, affordable solutions. Consequently, every major university in the Unites States offers dedicated graduate courses on the fundamentals of energy generation, conservation and transportation."--
Keywords: Power resources; Pollution